Effectiveness of Cognitive-behavioral Therapy for Generalized-Anxiety Disorders in Adolescents: A Systematic Review Using PICO Framework - Suryanto, Rajwa Dwifauza; Gaharani, Prodio Efa; Salsabila, Salma; Finola Aziz, Calista Sasikirana; Khaerani, Fitri Azlia; Athaya, Salsabila; Setyowati, Lulu Alya; Kartadikaria, Elisya; Djamaluddin, Muhammad Ilham; Soewahju, Renata Bella Aprilana; Pitaloka, Dian Ayu Eka (Pharmacology and Clinical Pharmacy Research, 2025)
A number of teenagers experience various levels of mental disorders, ranging from mild stress to Generalized Anxiety Disorder (GAD). According to the World Health Organization (WHO), approximately 264 million people suffer from anxiety disorders, including GAD, and this condition is a significant leading cause of suicide incidents, ranking sixth among serious mental health issues. From a societal perspective, Cognitive Behavioral Therapy (CBT) has the advantage of cost-effectiveness by minimizing the use of medications and enhancing productivity in education for adolescents receiving CBT. This study aims to conduct a systematic review of the existing literature on GAD in adolescents, using the PICO format method and formulating relevant research questions (RQ). Based on research that has been done, CBT has a relevant effect on some cases of GAD experienced by adolescents, although in some conditions CBT needs to be combined with antidepressants.